Robust radiogenomics approach to the identification of EGFR mutations among patients with NSCLC from three different countries using topologically invariant Betti numbers - Ninomiya, Kenta; Arimura, Hidetaka; Chan, Wai Yee; Tanaka, Kentaro; Mizuno, Shinichi; Nadia Fareeda, Muhammad Gowdh; Nur Adura, Yaakup; Liam, Chong Kin; Chai, Chee Shee; Ng, Kwan Hoong (PLOS, 2021)
Abstract Objectives: To propose a novel robust radiogenomics approach to the identification of epidermal growth factor receptor (EGFR) mutations among patients with non-small cell lung cancer (NSCLC) using Betti numbers (BNs).